2012
DOI: 10.1016/j.virol.2012.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Use of an in vivo animal model for assessing the role of integrin α6β4 and Syndecan-1 in early steps in papillomavirus infection

Abstract: Human papillomaviruses (HPV) are small DNA tumor viruses. HPV infection requires entry of virions into epithelial host cells that support the viral life cycle. Here, we used an in vivo mouse model, in which HPV pseudoviruses (PVs) are scored for their ability to transduce reporter genes, to test the role of various cellular proteins in entry. We initially investigated the role of integrin α6β4 in mediating early steps of HPV infection. Deficiency of integrin α6β4 modestly but significantly suppressed reporter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Wound healing facilitates HPV16 PsV infection of epithelial cells, as shown in the in vivo mouse vaginal challenge model (53). Although syndecan-1 may be the most prevalent, several HSPGs can potentially serve as binding receptors (54,55). At least in K562 cells (erythroleukemia cell line), which lack common HSPGs, exogenous expression of syndecan-1, syndecan-4, and glypican 1 enhanced HPV16 L1 VLP binding in correlation with the level of HSPG expression (54).…”
Section: Hpv16 Binding and Entrymentioning
confidence: 98%
See 1 more Smart Citation
“…Wound healing facilitates HPV16 PsV infection of epithelial cells, as shown in the in vivo mouse vaginal challenge model (53). Although syndecan-1 may be the most prevalent, several HSPGs can potentially serve as binding receptors (54,55). At least in K562 cells (erythroleukemia cell line), which lack common HSPGs, exogenous expression of syndecan-1, syndecan-4, and glypican 1 enhanced HPV16 L1 VLP binding in correlation with the level of HSPG expression (54).…”
Section: Hpv16 Binding and Entrymentioning
confidence: 98%
“…␣ 6 integrin was first identified as a candidate receptor using HPV6 L1 VLP on HaCaT cells (71). It has been demonstrated that the level of HPV16 PsV binding correlates with the levels of ␣ 6 /␤ 4 integrin, as decreasing ␣ 6 integrin expression through small interfering RNA (siRNA) significantly reduces HPV16 PsV infection (44), and that HPV16 PsV reporter gene transduction in ␤ 4 integrin knockout mice was significantly reduced (55). Further, activation of focal adhesion kinase (FAK) by HPV16 PsV is important for infection of HaCaT cells, and since this activation can be blocked through an ␣ 6 integrin blocking antibody in mouse embryonic fibroblasts, it may suggest that HPV16 PsV signals through ␣ 6 integrin to activate FAK (44).…”
Section: Hpv16 Binding and Entrymentioning
confidence: 99%
“…The proposed secondary HPV receptor integrin α6 can form complexes with either β1 or β4 integrins (Kligys et al, 2012). The possible roles of β subunits as a direct binding partner of HPV virions during infection were investigated, and these studies lead to the conclusion that neither β1 nor β4 showed any direct binding to viral particles (Evander et al, 1997; Huang and Lambert, 2012; Yoon et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…As syndecan-1 is the most abundant HSPG expressed on the surface of keratinocytes, it is logical to hypothesize that epithelium infected by HSV has localized increases in the levels of syndecan-1 and syndecan-2, potentially resulting in faster HSPG-mediated binding and subsequent conformational changes of the HPV16 capsid that expose the N terminus of L2 allowing for furin cleavage (Alexopoulou et al, 2007;Raff et al, 2013;Shafti-Keramat et al, 2003). Even though it has been shown that syndecan-1 knockout mice are susceptible to HPV infection, it remains clear that HSPGs play a vital role in initial targeting of virions to the basement membrane, coating of virions with growth factors and other events preceding viral entry (Huang & Lambert, 2012;Surviladze et al, 2012). In summary, our findings demonstrate that molecular changes caused by HSV to the cellular microenvironment promote HPV acquisition in vitro, providing the first evidence for a mechanism that explains the ongoing epidemiological link between HSV infection and HPVassociated cancers.…”
Section: Discussionmentioning
confidence: 99%